Bacterial (9A2H) enhancement alters the nematode community structure and decomposition pathway of amended nutrient-limited soil (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Luckyana DR, Puspitasari IGAAR, Maharning AR. 2020. Bacterial (9A2H) enhancement alters the nematode community structure and decomposition pathway of amended nutrient-limited soil. Biodiversitas 21: 4813-4820. This study examined the influence of paddy litter amendment and bacterial enhancement of nutrient-limited soil on the nematode community structure and investigated the decomposition rate of the litter due to the treatment. We applied a microcosm-based approach using sand as the medium, including the following treatments: no-bacteria, 9A-autotrophic-bacteria, 2H-heterotrophic-bacteria, and 9A-2H-mix-bacteria, with five replicates. The litter bag experiment and exponential decay model estimated the litter decomposition rate in the microcosm. The soil samples and litter bags were retrieved after days 21, 42, and 63. The structure, enrichment, channel index (CI), and canonical correspondence analysis were employed to investigate the nematode community response. Bacterial enhancement shifted the nematode community and the soil food web toward the dominant bacterial pathway by day 63 (CI: 0), with a slightly less structured food web that was supported by bacterivorous nematodes mostly related to available nutrients. These changes coincided with soil organic carbon and nitrogen increases over time. Our experiments showed that paddy litter amendment and the 9A, 2H, and 9A-2H-mix bacterial enhancements improved nutrient-limited soil, according to the analysis of the nematode community, its composition, and the food web conditions determining nutrient mobility and availability. However, these factors have no impact on the litter decay rate.
Keywords: Baerman funnel method, forest soil resource, nematode feeding group, paddy litter decomposition, soil food web index